A conceptual artistries multi-sided business model: upskilling and nurturing people with a financial imbalance in Bangladesh as fashion-preneurs - Nahid, Ahmad Ishtiak; Tasnia, Tasnuva; Hossain, Mokter; Ahmad Dahlan, Abdul Rahman (Kulliyyah of Information & Communication Technology, International Islamic University Malaysia, 2023)
To develop a conceptual Artistries business model including a digital platform and apps, in solving the key challenges, pains, gains & job-to-do of various customer segments (CS) for a clothing-related business. That will provide quality clothing products for the market while aligning with the Sustainable Development Goals (SDG) including reducing poverty (SDG1), promoting decent employment and economic growth (SDG8), and responsible consumption and production (SDG12). The situation has become difficult because of the global pandemic, particularly financially in Bangladesh. The lockdown in Bangladesh has caused a huge deal of financial crisis for the economy which also had an impact on commercial shops. This paper identifies the struggles and difficulties faced by the various CS - people in poverty and the poor, jobless or laid-off workers, buyers, sellers, and suppliers of clothing products & services. The Business Model Canvas (BMC) and Value Proposition Canvas tools were used as part of the Design Thinking (DT) approach, adapted by this paper. This paper attempts to offer various CS with a wide range of fashionable clothing options that encourage and support the fashion ecosystem. Owning our own cultural and native products on the market while maintaining quality. People in poverty, particularly unemployed workers, can acquire pertinent skills, materials, and financial assistance for their own solvency, and re- & up-skilling themselves to become environmental fashion entrepreneurs through the business model. That is connecting the Artistries brand with people in poverty, buyers, sellers, and donors while sustaining business profitability.